MODEL PENGEMBANGAN INFRASTRUKTUR TERMINAL KARGO DAN SMART LOGISTICS BERBASIS KONEKTIVITAS MULTIMODA DI BIJB KERTAJATI - Hafizh Sabda Adhiaska; Dini Rosmalia; Wahyu Dewanto; Sandy Lesmana (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
West Java International Airport (BIJB) Kertajati has strategic potential as a regional logistics distribution hub, supported by its connectivity to toll roads, industrial zones, and the Rebana metropolitan development. However, low levels of flight activity and kargo distribution have resulted in suboptimal utilization of the area. This study aims to identify the current state of multimodal logistics infrastructure and analyze the need for smart logistics infrastructure development in the BIJB Kertajati area. This study employs a quantitative-qualitative approach (mixed-methods) using Gap Analysis and SWOT analysis, reinforced by the IFAS-EFAS framework. Research data was collected through field observations, literature reviews, and an analysis of the area’s development policies. The results indicate that the BIJB Kertajati area possesses key strengths, including connectivity via the Cipali and Cisumdawu toll roads, the availability of extensive land, and a strategic location relative to industrial zones and the Port of Cirebon. However, the area still faces limitations, including low kargo activity, suboptimal multimodal integration, and limitations in the digital logistics system. The study produced a logistics infrastructure development model based on a kargo terminal, smart warehouse, digital logistics platform, and green infrastructure to support the efficiency of goods distribution and the sustainability of the area. This study is expected to serve as a reference for the development of airport-based logistics areas in Indonesia.